The impact of intellectual capital and managerial ability on the financial performance: an analysis on infrastructure, utilities and transportation companies in indonesia - Variyetmi Wira; Yenida, Yenida; Rahmita Sari (International Ecsis Association, 2023)
Intellectual capital is an intangible asset that is strategically owned by a firm in the expansion of a knowledge-based economy. Intangible assets require a favorable disclosure to afford value to the firm financial performance. This research aims to analyze the effect of the added value of intellectual capital, intellectual capital disclosure (ICD), and managerial ability on the firm financial performance. This research uses data from infrastructure companies, utilities, and transportation in Indonesia for the 2017-2020 period. The number of samples used in the research were 30 firms per year, so the total obtained 120 samples of the firm. The data was processed using the Stata 16 version application. The research results showed, that the variables researched such as the added value of intellectual capital (M-VAIC), IC disclosure (Intellectual Capital Disclosure-ICD) and managerial ability (MA) insignificantly affect the financial performance that measured with ROA, ROE, net profit margin-NPM, tobinsQ, and firm return.